Is titanium alloy Ti‐6Al‐4 V cytotoxic to gingival fibroblasts-A systematic review - Jonathan Willis; Siwei Li; St John Crean; Fadi N. Barrak (Wiley, 2021)
Abstract Objectives Grade V titanium alloy (Ti‐6Al‐4 V) is a well‐recognized metallic biomaterial for medical implants. There has been some controversy regarding the use of this alloy in medical devices in relation to the toxicity of vanadium. In Dentistry, Ti‐6Al‐4 V remains prevalent. This systematic review aims to evaluate the effects of Ti‐6Al‐4 V on cells relevant to oral environments such as gingival fibroblasts. Materials and methods A literature search was undertaken for relevant English language publications in the following databases: Dental and Oral Science, Medline and Web of Science. The electronic search was supplemented with a search of references. Results After application of inclusion and exclusion criteria. A total of eight papers are included in this review. These papers were all in vitro studies and were categorized into whole implant, discs, or implant particles based on the type of test materials used in the studies. Conclusion Based on the analyses of the eight included studies in this review, if Ti‐6Al‐4 V as a material is unchallenged, i.e., as a whole implant in pH neutral environments, there appears to be little effect on fibroblasts. If Ti‐6Al‐4 V is challenged through corrosion or wear (particle release), the subsequent release of vanadium and aluminium particles has an increased cytotoxic effect in vitro in comparison to commercially pure titanium, hence concerns should be raised in the clinical setting.